ROLE OF DEDUCTIBLES IN THE INSURANCE PROCESS - Volkova, Jeļena; Viškers, Evalds (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The application, type and amount of a deductible is one of the opportunities of changing the covering in insurance. The research on the deductible amount is currently especially important because there is severe competition in the Latvian insurance market among the insurers, and due to the market conjuncture, it is no longer possible to compete only by lowering the price. The theoretical studies have been summarized in the research on the essence and application of the deductible, which were implemented by foreign and Latvian scientists. The aim of the research is to characterise the essence of a deductible, to specify the applied definitions by providing the types of the deductible amount and by characterizing their effects on the insurance process. The following methods were used in the research: monographic, problem analysis, scientific induction and deduction methods, and adoption of a decision under conditions of uncertainty.